Adorno on popular culture - Witkin, Robert W. (Robert Winston) (International library of sociology., 2003)
Unpacks Adorno's critique of popular culture in an engagingly, looking at the development of theories of authority, commodification and negative dialectics. Goes on to consider Adorno's writing on specific aspects of popular culture.